L’assetto giuridico delle comunità israelitiche italiane nel primo decennio post-unitario (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. Il congresso israelitico di Ferrara (1863) - 3. Il disegno di legge Vacca del 1865 - 4. Il congresso israelitico di Firenze (1867) - 5. Conclusioni.The legal framework of the italian Jewish communities in the first decade of Italy’s unificationABSTRACT: The essay deals with the unification of the normative structures of the Italian Jewish communities after the Unity, by reconstructing the extensive debate that took place in the Jewish context. It then analyzes the legislative proposal of extending Rattazzi's law of 1857 to the entire national territory, which was presented by the Italian government to the Parliament in 1865. Finally, it gives an account, through a vast and largely unpublished archival documentation, both of the choice of individual communities to maintain the legal systems in force in the pre-unitary italian States, and of the attempts, advanced in the parliamentary center between the end of the nineteenth and the beginning of the twentieth century, of abrogation of the Rattazzi's law, considered, due to its jurisdictional traits, in contrast to the principles of the liberal State.